If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -14 = 49 Reorder the terms: -14 + 9x = 49 Solving -14 + 9x = 49 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 9x = 49 + 14 Combine like terms: -14 + 14 = 0 0 + 9x = 49 + 14 9x = 49 + 14 Combine like terms: 49 + 14 = 63 9x = 63 Divide each side by '9'. x = 7 Simplifying x = 7
| (8a^3)(b^3)+(27a^6)= | | 2x(x+4)(6)=16 | | 2w-5w=12 | | -5(3p+4)-10=4(4p+8) | | 8=y-10 | | -86+5y+6=5(3y-3)-5 | | 7(6x-8)=70 | | 5x^3+20x^2+20= | | 5(c-3)=6(c-6) | | 21x^2-5x-4=0 | | 4(3x+5)=44 | | 18=6x-12 | | y^4-y=0 | | 6x^4-24x^2=0 | | 3x^2+3x-7=0 | | m^2=-4 | | 18(5c-1)-16=88c+18 | | 104-92=32y-35y | | -15s-34+5(3s+8)=0 | | x-56=53 | | 12m-3m^2=9 | | 5m-11m=18 | | 8-8=19t-18t | | 3r-13r=20 | | 2(x+3)-4x=3x-2(2x-1) | | 10x+8=8x+9 | | -2+12=4b-8-3b | | 7x^2+5x-2=0 | | 12=x+4 | | 9u-56v+32= | | 13x=7x+30 | | 5+3(2n+5)-n= |